Pemanfaatan Teh Hijau sebagai Obat Kumur dalam Upaya Peningkatan Perekonomian Masyarakat Desa Talagasari dan Sindangsari: Utilization of Green Tea as Mouthwash in an Effort to Improve the Economy of the Talagasari and Sindangsari Village Communities - Kusmiyati, Mimin; Novani, Elvi Tri; Widyastuti, Tri; Purkon, Dicki Bakhtiar; Herdiana, Irvan; Noviapratami, Nikky; Fatimah, Cucu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Gingivitis is an oral health disease characterized by inflammation of the gingival tissue that appears reddish. One way to prevent and treat gingivitis is to use mouthwash. Green tea herbal mouthwash is used to treat gingivitis. Green tea is known to have antimicrobial activity that causes gingivitis. The increase in public knowledge about green tea mouthwash increased by 41%. This shows public understanding of the benefits of green tea mouthwash for preventing gingivitis and the economic value of green tea herbal mouthwash products.